Brimapitide Reduced Neuronal Stress Markers and Cognitive Deficits in 5XFAD Transgenic Mice. - Gourmaud, Sarah; Thomas, Priscilla; Thomasseau, Sylvie; Tible, Marion; Abadie, Claire; Paquet, Claire; Hugon, Jacques (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by accumulations of amyloid-β (Aβ42) and hyperphosphorylated tau proteins, associated with neuroinflammation, synaptic loss, and neuronal death. Several studies indicate that c-Jun N-terminal kinase (JNK) is implicated in the pathological features of AD. We have investigated in 5XFAD mice, the therapeutic effects of Brimapitide, a JNK-specific inhibitory peptide previously tested with higher concentrations in another AD model (TgCRND8). Three-month-old 5XFAD and wild-type littermate mice were treated by intravenous injections of low doses (10 mg/kg) of Brimapitide every 3 weeks, for 3 or 6 months (n = 6-9 per group). Cognitive deficits and brain lesions were assessed using Y-maze, fear-conditioning test, and histological and biochemical methods. Chronic treatment of Brimapitide for 3 months resulted in a reduction of Aβ plaque burden in the cortex of 5XFAD treated mice. After 6 months of treatment, cognitive deficits were reduced but also a significant reduction of cell death markers and the pro-inflammatory IL-1β cytokine in treated mice were detected. The Aβ plaque burden was not anymore modified by the 6 months of treatment. In addition to modulating cognition and amyloid plaque accumulation, depending on the treatment duration, Brimapitide seems experimentally to reduce neuronal stress in 5XFAD mice.

Dual Kinase Inhibition Affords Extended in vitro Neuroprotection in Amyloid-β Toxicity. - Gourmaud, Sarah; Mouton-Liger, François; Abadie, Claire; Meurs, Eliane F; Paquet, Claire; Hugon, Jacques (J Alzheimers Dis, 2016)
In Alzheimer's disease (AD), the amyloid cascade hypothesis proposes that amyloid-beta (Aβ) neurotoxicity leads to neuroinflammation, synaptic loss, and neuronal degeneration. In AD patients, anti-amyloid immunotherapies did not succeed because they were possibly administered late in AD progression. Modulating new targets associated with Aβ toxicity, such as PKR (double-stranded RNA dependent kinase), and JNK (c-Jun N-terminal kinase) is a major goal for neuroprotection. These two pro-apoptotic kinases are activated in AD brains and involved in Aβ production, tau phosphorylation, neuroinflammation, and neuronal death. In HEK cells transfected with siRNA directed against PKR, and in PKR knockout (PKR-/-) mice neurons, we showed that PKR triggers JNK activation. Aβ-induced neuronal apoptosis, measured by cleaved PARP (Poly ADP-ribose polymerase) and cleaved caspase 3 levels, was reduced in PKR-/- neurons. Two selective JNK inhibitory peptides also produced a striking reduction of Aβ toxicity. Finally, the dual inhibition of PKR and JNK nearly abolished Aβ toxicity in primary cultured neurons. These results reveal that dual kinase inhibition can afford neuroprotection and this approach is worth being tested in in vivo AD and oxidative stress models.